Maternal mortality report (London : The Maternal Mortality Committee)
1934-10 1934 1930s 19 pages (b) A subsidy to enable a midwife to practise in a district which would otherwise not support her. Ten County Boroughs operate this. (c) The appointment, where necessary, of municipal midwives. This power is used by nine only. We have only included midwives employed by municipal hospitals or nursing homes where these are specifically stated to be working on a district. (d) The payment of part fees to a midwife when the patient cannot afford the full fee. Thirty-one Boroughs appear to use this power. Several Authorities have an insurance scheme for mothers who may need the services of a doctor. (e) "Refresher" courses for practising midwives. Definite courses of lectures are provided by thirteen Borough Councils. We have not included odd groups of lectures to Health Visitors, &c., but only cases in which a definite post-graduate course is mentioned. (4) Maternity Homes or beds in a Maternity Hospital for :— (а) Complicated cases. Seventy-two Boroughs state they have beds. (b) Patients whose home circumstances are unsuitable for a confinement at home. Sixty-six Boroughs have beds. It is particularly difficult to get an accurate idea of this number as only a certain number of places specifically state the fact. It is probable that some "special circumstances", and "by arrangement", include these cases. (c) Ante-natal observation. We assume from the description of accommodation that beds would be available for these cases in fifty-nine Boroughs. (d) The treatment of puerperal sepsis. Sixty-eight Borough Councils would appear to have beds for this purpose. (5) Home Helps. Twenty-four Borough Councils state they provide these. (6) The Provision of Milk or Food during the last three months of pregnancy and during lactation. Sixty-nine state they provide this, but this number is probably under-estimated. (7) Complicated Midwifery. (a) The fees of doctors called in by midwives for an "emergency" in connection with a confinement must be paid, if necessary, in whole or in part. (7) 292/824/1/20